SEGMENTASI PASAR KOPI MENGGUNAKAN METODE KNN DI INDONESIA - Muhamad Maksum Hidayat; Wahyu Nugroho; Arief Setyanto (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Coffee is one of the most widely consumed plantation commodities in Indonesia and has great opportunities to be developed, especially in the field of market development. The thing that becomes an obstacle for coffee entrepreneurs is the right segmentation of the coffee market with the vast Indonesian state. This study aims to segment the coffee market in Indonesia by utilizing coffee image data available on Instagram social media with image classification using the K-Nearest Neighbor algorithm and histogram feature extraction, so as to determine the exact coffee market segmentation in Indonesia.